2010
DOI: 10.1177/1059601110378456
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Generalizability of Paternalistic Leadership: An Expansion of Leader-Member Exchange Theory

Abstract: Paternalism is an emerging concept with significant potential for international leadership research. Paternalistic leaders combine benevolence with authority. Paternalism is a prevalent leadership style in non-Western business organizations. In this article, the authors extend research on paternalism to the Western business context. They compare the attitudes of employees from the United States ( N = 215) and India ( N = 207) with respect to paternalistic leadership and its correlates. Paternalism had a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
223
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(242 citation statements)
references
References 58 publications
(70 reference statements)
11
223
0
8
Order By: Relevance
“…In the Chinese context, for example, individuals are used to a paternalistic leadership style (Farh & Cheng, 2000;Pellegrini, Scandura & Jayaraman, 2010;Ho & Nesbit, 2014;Chou, Sibley, Liu, Lin & Cheng, 2015). Also, Chinese individuals are likely to respond to a paternalistic leadership style by adopting subordinate behaviours aimed at demonstrating their indebtedness towards their leaders' benevolence (Ho & Nesbit, 2014).…”
Section: Leadership Stylementioning
confidence: 99%
“…In the Chinese context, for example, individuals are used to a paternalistic leadership style (Farh & Cheng, 2000;Pellegrini, Scandura & Jayaraman, 2010;Ho & Nesbit, 2014;Chou, Sibley, Liu, Lin & Cheng, 2015). Also, Chinese individuals are likely to respond to a paternalistic leadership style by adopting subordinate behaviours aimed at demonstrating their indebtedness towards their leaders' benevolence (Ho & Nesbit, 2014).…”
Section: Leadership Stylementioning
confidence: 99%
“…The generation of high values in relation to this scale reflect employee-manager relationships that are characterised by a great degree of affect, loyalty, contribution and professional respect. collectivistic societies such as Turkey where a 5.27 LMX mean score was reported in a study by Pellegrini and Scandura (2006) and a 4.86 LMX mean score was reported in India (Pellegrini et al, 2010). Pellegrini and colleagues used the seven-point scale of LMX, which is equivalent to the five-point scale applied in the present study (see appendix C; this will be discussed in more detail in section 7).…”
Section: Ranking Analysis Of Likert-type Scale: the Findings Of Lmx Qmentioning
confidence: 99%
“…Despite the research on managerial approaches and practices based on the cultural characteristics of western societies is abundant, the research reflecting cultural characteristics of eastern societies in the same field is scarce. On the other hand, recent research has frequently demonstrated that the leadership model based on paternalism phenomenon which reflects the dominant cultural characteristics of eastern societies is highly effective in those societies (Pellegrini et al, 2010). As substantial amount of studies show paternalistic leadership phenomenon is also a positive cultural value in our country.…”
Section: Introductionmentioning
confidence: 99%